Assessing the reach, effectiveness, adoption, implementation, and maintenance of the ProACTIVE SCI physical activity counseling intervention among physiotherapists and SCI peer coaches during the transition from rehabilitation to community - Olsen, Kenedy; Martin Ginis, Kathleen A.; Lawrason, Sarah; McBride, Christopher B.; Walden, Kristen; Le Cornu Levett, Catherine; Colistro, Regina; Plashkes, Tova; Bass, Andrea; Thorson, Teri; Clarkson, Ryan; Bitz, Rod; et al. (Frontiers in Neurology, 2023)
Introduction Physical Activity (PA) levels for individuals with spinal cord injury (SCI) peak during rehabilitation and sharply decline post-discharge. The ProACTIVE SCI intervention has previously demonstrated very large-sized effects on PA; however, it has not been adapted for use at this critically understudied timepoint. The objective is to evaluate the reach, effectiveness, adoption, implementation, and maintenance of the ProACTIVE SCI intervention delivered by physiotherapists and SCI peer coaches during the transition from rehabilitation to community. Methods A single-group, within-subjects, repeated measures design was employed. The implementation intervention consisted of PA counseling training, champion support, prompts and cues, and follow-up training/community of practice sessions. Physiotherapists conducted counseling sessions in hospital, then referred patients to SCI peer coaches to continue counseling for 1-year post-discharge in the community. The RE-AIM Framework was used to guide intervention evaluation. Results Reach: 82.3% of patients at the rehabilitation hospital were reached by the intervention. Effectiveness: Interventionists (physiotherapists and SCI peer coaches) perceived that PA counseling was beneficial for patients. Adoption: 100% of eligible interventionists attended at least one training session. Implementation: Interventionists demonstrated high fidelity to the intervention. Intervention strategy highlights included a feasible physiotherapist to SCI peer coach referral process, flexibility in timepoint for intervening, and time efficiency. Maintenance: Ongoing training, PA counseling tracking forms, and the ability to refer to SCI peer coaches at discharge are core components needed to sustain this intervention. Discussion The ProACTIVE SCI intervention was successfully adapted for use by physiotherapists and SCI peer coaches during the transition from rehabilitation to community. Findings are important for informing intervention sustainability and scale-up.